Biostratigraphy of the Small Shelly Fossils From the Upper Maidiping Formation (Terreneuvian) at the Fandian Section, Sichuan Province, South China - Feng, Qian; Pan, Bing; Yang, Aihua; Lu, Miao; Li, Guoxiang (Frontiers in Earth Science, 2022)
Small shelly fossils (SSFs) are a useful and critical tool for subdivision and correlation of the Cambrian Terreneuvian stratigraphy. The Maidiping Formation in southern Sichuan is a well-known Terreneuvian lithologic unit with rich SSFs. Here the upper Maidiping Formation at the Fandian section, an important supplementary section of the classic Maidiping section, is studied for understanding its SSF assemblages and stratigraphic implication. Altogether, there are 26 genera, 24 species and 3 undetermined species recovered from the Fandian section, and Watsonella crosbyi is discovered from this section for the first time. Two SSF biozones of the Yangtze Platform, i.e., the possible Paragloborilus subglobosus-Purella squamulosa Assemblage Zone (? Zone II) and the W. crosbyi Assemblage Zone (Zone III) can be recognized. Comparing with the Maidiping section, the Fandian section has a relatively successive SSF biostratigraphy and carbon isotope stratigraphy in the upper Maidiping Formation. The SSF Zone II (?) and III from the Fandian section can respectively correlate to the same zones from the upper Maidiping Formation of the nearby Maidiping section (only Zone III), the upper Zhongyicun and Dahai members of the Zhujiaqing Formation in eastern Yunnan, the top Kuanchuanpu Formation in southern Shaanxi and northern Sichuan, and the beds 4 and 5 (or units 3 and 4) of the Yanjiahe Formation in western Hubei. The almost cosmopolitan distribution and nearly synchronous earliest appearance of W. crosbyi strengthen the applicability of its first appearance datum (FAD) to define the base of the Cambrian Stage 2 in South China (Xiaotanian) as well as in other continents. The FAD of W. crosbyi just around the onset of the ZHUCE carbon isotope excursion at the Fandian section also further reinforces the utility of the onset of ZHUCE as an auxiliary maker for defining the base of the Xiaotanian in South China.